2017
DOI: 10.1111/resp.13199
|View full text |Cite
|
Sign up to set email alerts
|

Unexpandable lung from pleural disease

Abstract: Unexpandable lung is a common complication of malignant pleural effusions and inflammatory pleural diseases, such as pleural infection (e.g. empyema and complicated parapneumonic effusion) and noninfectious fibrinous pleuritis. Unexpandable lung due to pleural disease may be because of an active pleural process, and is referred to as malignant or inflammatory lung entrapment. An unexpandable lung may also be encountered in the setting of remote pleural inflammation resulting in a mature fibrous membrane overly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
1
37
0
1
Order By: Relevance
“…The ability of the lung to re-expand after pleural fluid withdrawal can be reliably assessed by measuring pleural pressure (P pl ) during thoracentesis. Thus, pleural manometry has been increasingly used to assess local abnormalities of lung mechanics in patients with pleural effusion (PE) [8][9][10]. While performing pleural manometry, we found that the pleural pressure curve showed oscillations resembling the pulse tracing line.…”
Section: Introductionmentioning
confidence: 81%
“…The ability of the lung to re-expand after pleural fluid withdrawal can be reliably assessed by measuring pleural pressure (P pl ) during thoracentesis. Thus, pleural manometry has been increasingly used to assess local abnormalities of lung mechanics in patients with pleural effusion (PE) [8][9][10]. While performing pleural manometry, we found that the pleural pressure curve showed oscillations resembling the pulse tracing line.…”
Section: Introductionmentioning
confidence: 81%
“…Consequently, the set consisting of a small-bore catheter, a pressure transducer and a urodynamics computer was used for continuous measurements of pleural pressure during fluid drainage. Interestingly, Table 1 Brief characteristics of three major patterns of pleural pressure changes during therapeutic thoracentesis [6,12,14,15,28,30].…”
Section: Methods Of Pleural Pressure Measurementmentioning
confidence: 99%
“…It should be emphasized that pleural manometry is the only method to calculate pleural elastance and evaluate lung expandability. These data are crucial in predicting the risk of unsuccessful pleurodesis [2,6,[9][10][11][12][13][14]. More data on the usefulness of pleural manometry in clinical practice were presented in a comprehensive review published recently [15].…”
Section: Introductionmentioning
confidence: 99%
“…2 The pleural aetiologies can be separated into lung entrapment and trapped lung. 3 Both lung entrapment and trapped lung are associated with the development of pleural effusion; however, the pathophysiology of these two conditions is different. Lung entrapment occurs in the setting of an active pleuropulmonary process, such as pneumonia, pleurisy or pleural malignancy.…”
Section: Descriptionmentioning
confidence: 99%